The imagetic-cognitive discursive argumentation of aspects of environmental sustainability in "charges" and cartoons: critical humor strategies through conceptual metaphors - Priscilla Chantal Duarte Silva; Maria Clotilde Almeida (Papéis: Revista do Programa de Pós-Graduação em Estudos de Linguagens - UFMS, 2020)
This study aims to investigate how the imagetic-cognitive discursive argumentation of cartoons and cartoons is built under the character of sustainability. Our goal is to demonstrate how argumentation can be understood from the cognitive point of view and how metaphors can be part of the argumentative game of these types of genres. The theoretical bias of Lakoff (1987; 2006) will be adopted to explain the metaphor on the cognitive plane, as a natural process of the human mind, that is, a form of thought. In the imagery of the genres under study, the analysis will be performed from Peirce's semiotics to understand the functioning of the image. Perelman's theory (1996) to explain the author's conception of argumentation as a form of persuasion. We observed the epididical discourses as those that appeal to socially shared values, that is, how environmental sustainability is conceptualized and understood. As a methodological character, the corpus linguistics will be carried out from a base analysis with textual data of speeches in “charges” and cartoons, published in the journalistic media for the composition of a corpus of analysis focused on environmental sustainability. Discourse analysis will be used to understand the argumentative scope of these discursive genres.